2011
DOI: 10.1016/j.phytochem.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical interaction between undamaged plants – Effects on herbivores and natural enemies

Abstract: Most research on plant-plant chemical interactions has focussed on events following herbivore or pathogen attack. However, undamaged plants also interact chemically as a natural facet of their behaviour, and this may have consequences for insects that use the plants as hosts. In this review, the links between allelopathy and insect behaviour are outlined.Findings on how chemical interactions between different plant species and genotypes affect aphid herbivores and their natural enemies are reviewed, and the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 78 publications
(88 reference statements)
0
39
0
1
Order By: Relevance
“…Volatile compounds released by undamaged plants also affect the attractiveness of neighbours to insect herbivores and insect natural enemies. Fewer aphids (Pettersson et al 1999;Glinwood et al 2004;Ninkovic et al 2009) and more aphid natural enemies (ladybirds and parasitoids) (Ninkovic and Pettersson 2003;Glinwood et al 2009) have been reported to be attracted to barley plants exposed to the volatiles emitted by undamaged weeds [Cirsium spp., Chenopodium album L.] or conspecifics (for reviews, see Ahman and Ninkovic 2010;Glinwood 2010;Ninkovic 2010;Glinwood et al 2011).…”
Section: Vocs Play Important Ecological Roles In Plant-plant Interactmentioning
confidence: 99%
“…Volatile compounds released by undamaged plants also affect the attractiveness of neighbours to insect herbivores and insect natural enemies. Fewer aphids (Pettersson et al 1999;Glinwood et al 2004;Ninkovic et al 2009) and more aphid natural enemies (ladybirds and parasitoids) (Ninkovic and Pettersson 2003;Glinwood et al 2009) have been reported to be attracted to barley plants exposed to the volatiles emitted by undamaged weeds [Cirsium spp., Chenopodium album L.] or conspecifics (for reviews, see Ahman and Ninkovic 2010;Glinwood 2010;Ninkovic 2010;Glinwood et al 2011).…”
Section: Vocs Play Important Ecological Roles In Plant-plant Interactmentioning
confidence: 99%
“…As well as using volatiles to determine taxonomic identity, aphids can also use plant volatiles to discriminate between the suitability of different plants within the same species (Webster 2012). The emission of volatiles from plants is significantly changed in plants under stress caused by abiotic factors (Gouinguene and Turlings 2002), mechanical damage (Piesik et al 2010), pathogens (Rajabaskar et al 2013b), herbivory (Arimura et al 2009), or co-existence with other con-and hetero-specific plants (Ninkovic et al 2002;Ninkovic 2003;Le Guigo et al 2012;Glinwood et al 2011) than in unstressed plants. These changes in their volatile profiles can play important roles in aphid behavior and host plant search.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, it has been shown that volatile interaction between unattacked plants 8 can also occur, reducing attractiveness of the receiving plants to insect herbivores. [9][10][11] Further, volatile interaction between unattacked plants can also lead to attraction of predatory insects, despite the absence of prey feeding on the plants. 8,12,13 Increasing diversity of plant species, or even the presence of different genotypes of the same plant species within an environment, has an impact on the abundance of phytophagous insects and their natural enemies.…”
mentioning
confidence: 99%